12. FACTORS AFFECTING THE RESULT OF TUBERCULOSIS TREATMENT AMONG CHILDREN ADMITTED TO PEDIATRIC DEPARTMENT OF NATIONAL LUNG HOSPITAL FROM 2017 TO 2020 (Vietnam Journal of Community Medicine, 2024)
Objective: To identify factors affecting the results of treatment of tuberculosis in children at the Department of Pediatrics - National Lung Hospital.Research method: Prospective descriptive study.Results: The results of tuberculosis treatment among 320 pediatric patients at the Department of Pediatrics - National Lung Hospital showed that: The successful treatment rate (cured and completed treatment) was 95.9%; the dropped-out rate was 1.9% treatment; the death rate was 2.2%; the prolonging treatment time was 11.6%; the sequelae were 7.5%; the readmission rate during outpatient treatment was 35.3%. There was no difference in treatment success rates according to bacteriological evidence; the pulmonary and extrapulmonary tuberculosis; and the age group. The treatment success rate was lower in the multi-organ TB group and the group whose disease was detected later than 2 months. The mortality rate was higher in the multi-organ TB group (3 organs: 27.3%); and the illness duration of more than 2 months (11.7%). Treatment drop out was most common in children less than 5 years old (2.6%). The proportion of pediatric patients with prolonged treatment was higher in the pulmonary tuberculosis group (15.2%); in the groups of less than 5 years old and group from 10-15 years old (13.5% and 13.8% respectively); and in the TB diagnosis group with bacterial evidence (18.5%). The readmission rate was higher in the group of less than 5 years old (48.4%) and Tuberculosis in 3 organs (81.8%); and Tuberculosis in 4 organs (33.3%). The sequelae occurred mainly in extrapulmonary tuberculosis (16.5%) and 3-organ tuberculosis (9.1%).Conclusion: The results of tuberculosis treatment in children were related to age, bacteriological evidence, type of tuberculosis, number of organs affected by tuberculosis and time of disease detection.
Keywords: Childhood tuberculosis; treatment of paediatric tuberculosis; results of tuberculosis treatment in children; pediatric tuberculosis.